Preparation method of high-toughness polyimide nanofiber film

By regulating the solvent composition of the polyimide nanofiber membrane spinning liquid and optimizing the fiber morphology, the problems of poor mechanical properties and insufficient toughness of the polyimide nanofiber membrane are solved, and the preparation of PI nanofiber membranes with high strength, high toughness and high porosity are achieved, which is suitable for oil-water separation applications.

CN119777073AActive Publication Date: 2025-04-08BEIHANG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411935753.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-08
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

In preparation and application, polyimide nanofiber membranes face problems such as high requirements for spinning liquid properties, poor mechanical properties and insufficient toughness, resulting in complex preparation process and unstable performance.

Method used

By regulating the composition of solvents in the PAA spinning liquid, mixed solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, etc. are used to adjust the viscosity and properties of the spinning liquid, optimize the fiber morphology, and thus improve the mechanical properties of the PI nanofiber membrane.

Benefits of technology

It significantly improves the break strength and elongation of break of PI nanofiber membrane, improves the fiber morphology, improves the mechanical properties and stability of the membrane, and is suitable for oil-water separation applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of polyimide film preparation, in particular to a preparation method of a high-toughness polyimide nanofiber film. The preparation method comprises the step of synthesizing polyamide acid, and further comprises the step of regulating and controlling the properties of a spinning solution containing the polyamide acid, a mixed solvent adopted for regulating and controlling the properties of the spinning solution is selected from at least two of N, N-dimethylformamide, N, N-dimethylacetamide, N-methyl pyrrolidone, dimethyl sulfoxide, 1, 4-dioxane, methanol, ethanol, methylbenzene, chloroform, tetrahydrofuran, normal hexane, normal heptane and normal decane. The breaking strength of the film can reach 30 MPa, the elongation at break can reach 60%, various diamine and dianhydride monomers and solvent systems can be prepared through the method, the mechanical performance is improved, the preparation technology is wide in application range, and the polyimide film prepared through the method can be used for oil-water separation and has the recycling and hot oil separation capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyimide film preparation, and in particular to a method for preparing a high-toughness polyimide nanofiber film. Background Art

[0002] In view of the increasingly severe energy and environmental problems, the development of organic membrane materials with excellent heat resistance and adjustable pore size and distribution has become a key demand in the field of water treatment and membrane technology. Polyimide (PI) has excellent mechanical properties, easy structural design, hydrolysis resistance, radiation resistance, solvent resistance and high temperature resistance, which makes PI widely used in aerospace, electronics and biomedicine. At the same time, the nanofiber membrane prepared by electrospinning not only has excellent structural controllability, but also has high porosity, which helps to significantly improve the efficiency of water treatment.

[0003] However, PI nanofiber membranes still face some challenges in preparation and practical application. First, in order to spin electrospun membranes with uniform fiber morphology, high requirements are placed on the polyamic acid (PAA) spinning solution. PAA spinning solutions with low molecular weight or low solid content are prone to a large number of beaded morphologies or failure to form membranes during the electrospinning process, while spinning solutions with high molecular weight and high solid content are too viscous to be electrospun. Therefore, the properties of the spinning solution are important process parameters for preparing PI nanofiber membranes with uniform morphology and stable performance. Secondly, the nanofiber membranes prepared by electrospinning will have poor overall mechanical properties due to uneven fiber morphology and random arrangement. In addition, PI itself has more rigid structures and strong interaction forces between molecular chains, which makes it insufficient in toughness and easy to be damaged during long-term use, limiting its stability and durability in use. In order to improve the mechanical properties of PI nanofiber membranes, researchers have explored a variety of methods, including monomer design, cross-linking and blending modification, but these methods are usually costly, complex processes and not universal. Therefore, improving the spinnability of PAA spinning solution and the mechanical properties of PI nanofiber membrane through simple, controllable and universal process optimization has important scientific and practical significance for the design, preparation and application of PI electrospinning nanofiber membrane. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a high-toughness polyimide nanofiber film and a preparation method thereof.

[0005] In the first aspect, the present invention provides a method for preparing a high-toughness polyimide nanofiber film, the preparation method comprising the step of synthesizing polyamic acid, and also comprising the step of regulating the properties of a spinning solution containing the polyamic acid; the mixed solvent used for regulating the properties of the spinning solution is selected from at least two of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, 1,4-dioxane, methanol, ethanol, toluene, chloroform, tetrahydrofuran, n-hexane, n-heptane, and n-decane. The present invention finds that by regulating the composition of the solvent in the PAA spinning solution, the properties of the spinning solution are significantly affected. Under the premise of not changing the solid content of the PAA spinning solution, the viscosity of the spinning solution can be increased or decreased as required to obtain a PAA spinning solution with better spinnability. This regulation can optimize the morphology of the fiber, so that a large number of beading defects in the fiber prepared from the PAA spinning solution with low solid content or low molecular weight disappear, and the uniform fiber morphology can directly promote the improvement of the mechanical properties of the nanofiber membrane.

[0006] Preferably, the method for preparing the high-toughness polyimide nanofiber film comprises the following steps: 1) Synthesis of polyamic acid: Aromatic dianhydride and diamine are used as raw materials for polycondensation to obtain a polyamic acid (PAA) solution with a high solid content.

[0007] 2) Controlling the properties of the spinning solution: The high solid content polyamic acid solution is mixed and stirred with the mixed solvent to obtain a polyamic acid spinning solution.

[0008] 3) Preparation of polyamic acid nanofiber membrane: electrospinning the polyamic acid spinning solution to obtain a polyamic acid nanofiber membrane.

[0009] 4) Preparation of polyimide nanofiber membrane: The polyamic acid nanofiber membrane is thermally imidized to obtain a high-toughness polyimide (PI) nanofiber film.

[0010] Preferably, in step 2), the mixed solvent comprises a first solvent and a second solvent, the first solvent is selected from one or more of N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, 1,4-dioxane, methanol, ethanol, toluene, chloroform, tetrahydrofuran, n-hexane, n-heptane, and n-decane; and / or the second solvent is N,N-dimethylformamide.

[0011] Preferably, the ratio of the first solvent to the second solvent is 10:90 to 60:40 w / w, for example, 10:90, 20:80, 25:75, 30:70, 35:65, 40:60, 50:50, 60:40, etc. and any value and range therebetween.

[0012] In some preferred embodiments provided by the present invention, the first solvent is 1,4-dioxane, and the second solvent is N,N-dimethylformamide, and the suitable usage ratio of the two is preferably 20:80~50:50, for example 20:80, 30:70, 40:60, 50:50.

[0013] Further preferably, in step 1), the aromatic dianhydride is selected from one or more of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, hexafluoroisopropylphthalic anhydride, and 4,4'-biphenyl ether dianhydride, and 3,3',4,4'-biphenyltetracarboxylic dianhydride is a more advantageous choice.

[0014] Further preferably, the diamine is selected from one or more of 4,4'-diaminodiphenyl ether, m-phenylenediamine, 4,4'-diaminobiphenyl, p-phenylenediamine, and 3,4-diaminodiphenyl ether. When the diamine is 4,4'-diaminodiphenyl ether, its ether bond provides a certain flexibility for the molecular chain, which can further enhance the toughness of the PI nanofiber membrane.

[0015] The molar ratio of the aromatic dianhydride to the diamine is preferably 0.96:1 to 1.03:1, and a more suitable amount is 1.01:1, for example, to ensure an equal group ratio between the anhydride and the amino group, so as to better improve the molecular weight of the synthesized PAA.

[0016] Preferably, the solvent of the polyamic acid solution is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; and the mass fraction of the polyamic acid solution is 10-20wt%.

[0017] Further preferably, the preparation method further comprises the step of purifying the aromatic dianhydride and the diamine; the purification method of the aromatic dianhydride is selected from one or more of heating, recrystallization of acetic anhydride, and vacuum sublimation, and the purification method of the diamine is selected from one or more of recrystallization and vacuum sublimation.

[0018] Further preferably, in step 1), the polycondensation reaction is carried out in a nitrogen atmosphere, the reaction temperature is 15-30°C, preferably room temperature, and the reaction time is 6-12 h.

[0019] According to a specific embodiment of the present invention, the specific steps of synthesizing the polyamic acid include: dissolving diamine in N,N-dimethylformamide, passing nitrogen protection, mechanically stirring at room temperature, slowly adding dianhydride, the total polycondensation reaction time is 6 to 12 hours, the molar ratio of aromatic dianhydride to diamine is 0.96:1 to 1.03:1, the mass fraction of PAA solution is 10 to 20 wt%, and the viscosity of PAA solution is 3×10 4 ~2×10 6 mPa·s.

[0020] Further preferably, in step 2), the mass fraction of the polyamic acid spinning solution is 10-15 wt %.

[0021] Further preferably, in step 3), the voltage of the high-voltage electrostatic field is 10-30 kV, the receiving distance is 10-20 cm, the receiving device is a flat plate, and the injection speed is 0.5-1.0 mL / h.

[0022] According to a specific embodiment of the present invention, the preparation method of the high-toughness polyamic acid nanofiber membrane is electrospinning, and the more preferred process parameters are: the high-voltage electrostatic field voltage is 10~30 kV, the receiving distance is 10~20 cm, the volume of the solution in the syringe is 0.5~2 mL, the receiving device is a flat plate, the injection speed is 0.5~1.0 mL / h, and the mixed solution is continuously electrospun to obtain a fiber film with a thickness of 10~200 μm. After spinning, the fiber film is torn off with pointed tweezers and the shape and size of the film is arbitrarily cut with surgical scissors.

[0023] Further preferably, in step 4), thermal imidization is carried out in a staged heating manner; preferably, the temperature is raised to 70-90 °C at a heating rate of 3-8 °C / min and kept warm for 30-50 min, then the temperature is raised to 130-170 °C for 0.8-1.2 h and kept warm for 1-1.2 h, then the temperature is raised to 330-370 °C for 0.8-1.2 h and kept warm for 1-1.2 h.

[0024] According to a specific embodiment of the present invention, the imidization method of the polyamic acid film is a staged temperature increase thermal imidization, and the specific process parameters include: heating from room temperature to 80°C at a heating rate of 5°C / min and keeping warm for 40 min, heating from 80°C for 1 h to 150°C and keeping warm for 1 h, heating from 150°C for 1 h to 350°C and keeping warm for 1 h, and naturally cooling. The above-mentioned staged temperature increase thermal imidization can ensure that PAA is completely imidized to PI.

[0025] In the present invention, a high-strength, high-toughness, high-porosity, and uniform PI nanofiber membrane can be prepared by the above method. Compared with the PI nanofiber membrane without the regulation of the spinning solution properties, the fiber morphology is greatly improved after the regulation, the beads gradually decrease and disappear, and the fiber morphology gradually becomes uniform. The corresponding fiber membrane has a fracture strength that can be increased from 2 MPa to 30 MPa, and a fracture elongation that can be increased from 8% to 60%. Thanks to the improvement of its mechanical properties and the solvent resistance and high temperature resistance of PI, the PI nanofiber membrane can be used as a self-supporting film for oil-water separation applications, and it exhibits recycling and hot oil separation capabilities.

[0026] In a second aspect, the present invention provides a high-toughness polyimide nanofiber film, which is prepared by the above-mentioned preparation method.

[0027] Preferably, the high-toughness polyimide nanofiber film has a breaking strength of 14-30 MPa and an elongation at break of 20-60%.

[0028] In a third aspect, the present invention provides the above-mentioned preparation method or the application of the above-mentioned high-toughness polyimide nanofiber membrane in oil-water separation. The high-toughness polyimide nanofiber membrane provided by the present invention is applied to oil-water separation and has excellent performances such as good recycling and hot oil separation.

[0029] The beneficial effects of the present invention are at least that: the preparation method of the high-toughness polyimide nanofiber film provided by the present invention utilizes the influence of the mixed solvent on the properties of the spinning solution to improve the morphology of the electrospun fiber, thereby effectively improving the mechanical properties of the PI nanofiber membrane, especially improving the toughness. Different from a large number of reported methods for improving the mechanical properties of PI, such as monomer design, cross-linking, and blending modification, the regulation of the spinning solution does not require complex post-treatment, the process operation is simple and easy, and can be used as a general method, which has important scientific significance for guiding the design of the electrospinning membrane system and the adjustment of process parameters. The high-toughness PI nanofiber membrane prepared by this method has excellent separation performance, temperature resistance and recyclability in oil-water separation applications, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 These are scanning electron microscope photos of the polyimide nanofiber membranes in Examples 1-6 of the present invention and Comparative Examples 1-3.

[0032] Figure 2 The mechanical properties of the polyimide nanofiber membranes in Examples 2 and 5 of the present invention and Comparative Example 2.

[0033] Figure 3 : It is the contact angle of the polyimide nanofiber membrane in Examples 2 and 5 of the present invention and Comparative Example 2. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] If no specific technology or conditions are specified in the embodiments of the present invention, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the devices, instruments, reagents, etc. is not specified, they are all conventional products that can be purchased through regular channels. The raw materials used in the present invention can be easily purchased in the domestic product market.

[0036] In the following embodiments of the present invention, the purification of aromatic dianhydride is carried out by vacuum sublimation, and the purity is greater than 99.9%. The purification of diamine is carried out by vacuum sublimation, and the purity is greater than 99.9%.

[0037] Example 1 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof. The aromatic dianhydride used is 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), the diamine used is 4,4'-diaminodiphenyl ether (ODA), and the solvent is N,N-dimethylformamide (DMF) and 1,4-dioxane (Diox).

[0038] The method for preparing the high-toughness polyimide nanofiber film provided in this embodiment comprises the following specific steps: 1) Synthesis of polyamic acid: First, BPDA and ODA were purified, and the molar ratio of BPDA:ODA was 1:1. The solvent was DMF. The polycondensation reaction was carried out for 12 h under mechanical stirring at room temperature. After the reaction was completed, the viscosity was tested to prepare a 20 wt% PAA solution.

[0039] 2) Preparation of spinning solution: Weigh 20wt% PAA solution, dilute with DMF and Diox to prepare PAA spinning solution, test the viscosity, the solid content of PAA spinning solution is 10wt% 、 The ratio of Diox:DMF is 20:80.

[0040] 3) Preparation of PAA nanofiber membrane: The prepared PAA spinning solution was transferred to a syringe for electrospinning. The positive DC voltage used was 13 kV and the negative DC voltage was -5 kV. The volume of the solution in the syringe was 2 mL, and the speed of the solution in the syringe was 1 mL / h. The receiving device was a flat plate with a layer of electrospinning release paper attached to the surface, that is, the fibers were not oriented. The distance between the needle and the receiving device was 15 cm. The mixed solution was continuously electrospun. After spinning, the fiber film could be torn off with pointed tweezers and dried overnight at room temperature and atmospheric pressure.

[0041] 4) Preparation of PI nanofiber membrane: The PAA nanofiber membrane was cut into appropriate sizes and heated in stages in an air atmosphere for thermal imidization treatment. The specific heating process parameters were: starting from room temperature, heating to 80°C at a heating rate of 5°C / min and keeping warm for 40 min, heating from 80°C for 1 h to 150°C for 1 h, heating from 150°C for 1 h to 350°C for 1 h, and naturally cooling to finally prepare the PI nanofiber membrane.

[0042] Example 2 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof, which is different from Embodiment 1 in that the solid content of the spinning solution used is 12.5 wt %.

[0043] Example 3 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof, which is different from Embodiment 1 in that the solid content of the spinning solution used is 15 wt %.

[0044] Example 4 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof, which is different from Embodiment 1 in that the ratio of Diox:DMF used is 50:50.

[0045] Example 5 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof, which is different from Embodiment 2 in that the ratio of Diox:DMF used is 50:50.

[0046] Example 6 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof, which is different from Embodiment 3 in that the ratio of Diox:DMF used is 50:50.

[0047] Example 7 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof. The difference from Embodiment 2 is that Diox is replaced by methanol, and the solvent used is a mixed solvent prepared by N,N-dimethylformamide (DMF) and methanol (MeOH).

[0048] Example 8 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof. The difference from Example 2 is that Diox is replaced by ethanol, and the solvent used is a mixed solvent prepared by N,N-dimethylformamide (DMF) and ethanol (EtOH).

[0049] Example 9 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof. The difference from Embodiment 2 is that Diox is replaced by toluene, and the solvent used is a mixed solvent prepared by N,N-dimethylformamide (DMF) and toluene (Tol).

[0050] Example 10 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof. The difference from Embodiment 2 is that Diox is replaced by chloroform, and the solvent used is a mixed solvent prepared by N,N-dimethylformamide (DMF) and chloroform (TCM).

[0051] Embodiment 11 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof, which is different from Example 2 in that Diox is replaced by tetrahydrofuran, and the solvent used is a mixed solvent prepared by N,N-dimethylformamide (DMF) and tetrahydrofuran (THF).

[0052] Example 12 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof. The difference from Embodiment 2 is that Diox is replaced by n-hexane, and the solvent used is a mixed solvent prepared by N,N-dimethylformamide (DMF) and n-hexane (Hexane).

[0053] Embodiment 13 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof. The difference from Embodiment 2 is that Diox is replaced by n-heptane, and the solvent used is a mixed solvent prepared by N,N-dimethylformamide (DMF) and n-heptane (Heptane).

[0054] Embodiment 14 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof. The difference from Embodiment 2 is that Diox is replaced by n-decane, and the solvent used is a mixed solvent prepared from N,N-dimethylformamide (DMF) and n-decane (Decane).

[0055] Embodiment 15 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof. The difference from Example 2 is that Diox is replaced by N,N-dimethylacetamide, and the solvent used is a mixed solvent prepared by N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMAc).

[0056] Example 16 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof. The difference from Example 2 is that Diox is replaced by N-methylpyrrolidone, and the solvent used is a mixed solvent prepared by N,N-dimethylformamide (DMF) and N-methylpyrrolidone (NMP).

[0057] Embodiment 17 This embodiment provides a high-toughness polyimide nanofiber film and a preparation method thereof. The difference from Embodiment 2 is that Diox is replaced by dimethyl sulfoxide, and the solvent used is a mixed solvent prepared by N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).

[0058] Comparative Example 1 The same method as in Example 1 was used, except that the spinning solution preparation step did not use a mixed solvent for dilution, and the solvent used was only N,N-dimethylformamide (DMF), and the solid content of the spinning solution was still 10 wt%.

[0059] Comparative Example 2 The difference from Comparative Example 1 is that the solid content of the spinning solution is 12.5 wt %.

[0060] Comparative Example 3 The difference from Comparative Example 1 is that the solid content of the spinning solution is 15 wt %.

[0061] The viscosity of the PAA spinning solution prepared in Examples 1-17 and Comparative Examples 1-3 was tested according to the relevant criteria of the national standard GB / T 22235-2008. The tensile strength and elongation at break of the prepared high-toughness polyimide nanofiber membrane were tested according to the relevant criteria of the national standard GB / T 1040.3-2006, with a tensile rate of 5 mm / min. Some test results are shown in Table 1 below.

[0062] Table 1

[0063] It can be seen from the results in Table 1 that the method of the present invention can adjust the viscosity of the spinning solution. Without changing the solid content, the viscosity can be increased or decreased to a viscosity range suitable for electrospinning conditions, which significantly improves the spinnability of the spinning solution and broadens the selection range of the molecular weight and solid content of the spinning solution. At the same time, the fiber morphology of the prepared PI nanofiber membrane is significantly improved, and the uneven beaded morphology is reduced to disappear. The improvement in morphology and the solvent effect improve the mechanical properties of the PI nanofiber membrane, such as Figure 1 , Figure 2 shown.

[0064] Embodiment 18 In this embodiment, an experimental method for the application of high-toughness polyimide nanofiber membrane in oil-water separation is provided. The PI nanofiber membrane prepared in Examples 1-17 is clamped between two glass tubes to build an oil-water separation device. The device is placed vertically, and 10 ml of a mixed solution of oil: water (1:1, V / V) is poured into it. The oil is allowed to pass through the membrane under its own gravity, and the oil phase passing through the membrane time and the amount of retained water are recorded. The separation flux (Flux) of the membrane and the separation efficiency (SE) of the membrane are calculated. In the oil-water mixed solution, the oil phase is one of dichloromethane, chlorobenzene, n-hexane, n-decane, and vegetable oil. In order to easily distinguish the oil phase from the water phase, the oil phase is dyed red with Nile red, and the water phase is dyed blue with methyl blue.

[0065] like Figure 3 As shown, the water contact angle of the PI nanofiber membrane prepared by Examples 1-17 is 120-129°, and the membrane has strong hydrophobicity and can meet the application requirements of oil-water separation. The membrane separation flux can reach 10518.83 Lm -2 h -1 , the separation efficiency exceeded 95%, and there was no obvious flux loss in the 6-cycle separation experiment, proving that it has the ability to be recycled. At the same time, the membrane can achieve the separation of 80°C hot oil-water mixture without membrane damage and loss of separation performance, and has the ability to separate hot oil. Some contact angles and the oil-water separation test results of the mixed solution of dichloromethane and water are shown in Table 2 below.

[0066] Table 2

[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high-toughness polyimide nanofiber film, comprising the step of synthesizing polyamic acid, characterized in that: The method also includes the step of regulating the properties of the spinning solution containing the polyamic acid; the mixed solvent used for the property regulation is selected from at least two of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, 1,4-dioxane, methanol, ethanol, toluene, chloroform, tetrahydrofuran, n-hexane, n-heptane and n-decane.

2. The method for preparing the high-toughness polyimide nanofiber film according to claim 1, characterized in that: The following steps are involved: 1) Synthesis of polyamic acid: Aromatic dianhydride and diamine are used as raw materials for polycondensation reaction to obtain a polyamic acid solution with a high solid content; 2) Controlling the properties of the spinning solution: mixing and stirring the high solid content polyamic acid solution and the mixed solvent to obtain a polyamic acid spinning solution; 3) Preparation of polyamic acid nanofiber membrane: electrospinning the polyamic acid spinning solution to obtain a polyamic acid nanofiber membrane; 4) Preparation of polyimide nanofiber membrane: The polyamic acid nanofiber membrane is subjected to thermal imidization to obtain a high-toughness polyimide nanofiber film.

3. The method for preparing the polyimide nanofiber film according to claim 2, characterized in that: In step 2), the mixed solvent includes a first solvent and a second solvent, the first solvent is selected from one or more of N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, 1,4-dioxane, methanol, ethanol, toluene, chloroform, tetrahydrofuran, n-hexane, n-heptane, and n-decane; the second solvent is N,N-dimethylformamide; Preferably, the ratio of the first solvent to the second solvent is 10:90~60:40 w / w.

4. The method for preparing the high-toughness polyimide nanofiber film according to claim 2 or 3, characterized in that: In step 1), the aromatic dianhydride is selected from one or more of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, hexafluoroisopropylphthalic anhydride, and 4,4'-biphenyl ether dianhydride; And / or, the diamine is selected from one or more of 4,4'-diaminodiphenyl ether, m-phenylenediamine, 4,4'-diaminobiphenyl, p-phenylenediamine, and 3,4-diaminodiphenyl ether; and / or, the molar ratio of the aromatic dianhydride to the diamine is 0.96:1 to 1.03:1; And / or, the solvent of the polyamic acid solution is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; preferably, the mass fraction of the polyamic acid solution is 10-20wt%.

5. The method for preparing the high-toughness polyimide nanofiber film according to claim 4, characterized in that: In step 1), the polycondensation reaction is carried out in a nitrogen atmosphere, the reaction temperature is 15-30°C, and the reaction time is 6-12 h.

6. The method for preparing a high-toughness polyimide nanofiber film according to any one of claims 2 to 5, characterized in that: In step 2), the mass fraction of the polyamic acid spinning solution is 10-15 wt %.

7. The method for preparing a high-toughness polyimide nanofiber film according to any one of claims 2 to 6, characterized in that: In step 3), the voltage of the high-voltage electrostatic field is 10-30 kV, the receiving distance is 10-20 cm, the receiving device is a flat plate, and the injection speed is 0.5-1.0 mL / h.

8. The method for preparing a high-toughness polyimide nanofiber film according to any one of claims 2 to 7, characterized in that: In step 4), thermal imidization is carried out in a staged heating manner; preferably, the temperature is raised to 70-90 °C at a heating rate of 3-8 °C / min and kept warm for 30-50 min, then the temperature is raised to 130-170 °C for 0.8-1.2 h and kept warm for 1-1.2 h, then the temperature is raised to 330-370 °C for 0.8-1.2 h and kept warm for 1-1.2 h.

9. A high-toughness polyimide nanofiber film, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the preparation method according to any one of claims 1 to 8 or the high-toughness polyimide nanofiber membrane according to claim 9 in oil-water separation.

Citation Information

Patent Citations

  • Method for preparing polyimide fibers

    CN102168317A

  • Polyimide nano-fiber membrane with crosslinked structure and preparation thereof

    CN102766270A

  • Method for preparing two-step synthesized polyimide-based micro / nano fibers

    CN105040120A

  • Highly-flexible coaxial cellulose acetate-polyimide electrostatic spinning fiber membrane used for oil-water separation

    CN105274732A

  • Firecracker-shaped titanium dioxide / polyimide nano hybrid fiber preparation method

    CN105625020A